Real-world use of imipenem/cilastatin/relebactam for the treatment of KPC-producing Klebsiella pneumoniae complex and difficult-to-treat resistance (DTR) Pseudomonas aeruginosa infections: a single-center preliminary experience - Leanza, Cristiana; Mascellino, Maria Teresa; Volpicelli, Lorenzo; Covino, Sara; Falletta, Antonio; Cancelli, Francesca; Franchi, Cristiana; Carnevalini, Martina; Mastroianni, Claudio M.; Oliva, Alessandra (Frontiers in Microbiology, 2024)
Carbapenem-resistant Enterobacterales (CRE) and difficult-to-treat Pseudomonas aeruginosa (DTR-PA) infections constitute an arduous clinical challenge due to limited treatment options. Among the new available drugs, imipenem/relebactam exhibits high activity towards DTR-PA and CRE, including KPC producing Klebsiella pneumoniae. Nevertheless, real life experiences with IMI/REL are still scant, especially with regard to KPC producing Klebsiella pneumoniae exhibiting resistance or high MICs to ceftazidime/avibactam. We present a real-life experience with the successful use of imipenem/cilastatin/relebactam for the treatment of KPC-producing Klebsiella pneumoniae complex including strains with resistance to ceftazidime/avibactam and difficult-to-treat Pseudomonas aeruginosa infections, including pneumonia and bone infections. We believe this study fits well with the scope of the Journal and the Research Topic entitled "New Therapeutic Strategies Against Carbapenem-Resistant Gram-negative Bacteria" and adds important information on the safe and successful use of imipenem/relebactam for complex infections caused by KPC producing Klebsiella pneumoniae complex (including those caused by strains resistant to ceftazidime/avibactam) and DTR-PA